Domestic/Care Work and Severe Exploitation. The Limits of Italian Migrant Regularization Schemes - Degani, Paola (Frontiers in Human Dynamics, 2022)
In Western Europe, migrant women are very often employed in the area of domestic/care work. In Italy, their presence in this sector is very important, making them particularly susceptible to abuse and exploitation. Domestic/care workers are a gendered segment of labor migration still strongly divided along a gender binary through the sexual division of roles and labor, directly associated with the sphere of the welfare state. Migrant women in the caregiving and domestic sector are one of the least protected work groups under international and national labor legislation. For a long time, waged domestic work has not been regarded as “actual” work, as it revolves around natural tasks that women perform in the household. In Italy, the domestic work sector has recently responded to a law-decree to regulate the presence of migrant workers in areas where there is an important presence of severe exploitation. The Italian government, in May 2020, to relaunch a post-pandemic economy released a Decree titled “Emergence of employment relationships” to counteract undeclared migrant work. From the data published by the Ministry of the Interior, 85% of the total number of applications submitted involved domestic and care workers, while the remaining 15% regarded subordinate work, especially in agriculture. Evidence of widespread irregularity of foreign women employed in this sector emerged only in part. Currently, unprecedented attention as well as institutional interest have been given to severe exploitation in the labor market rather than to forced prostitution or other forms of heavy servitude to the detriment of foreigners (i.e., begging, forced criminal activities). Identification and assistance to migrants involved in severe labor exploitation however include an “extraordinary” number of young male adults which are receiving unprecedented attention. The article analyzes the effects of recent regularization of the domestic/care work and the outcome on migrant women during the critical COVID-19 pandemic period produced by this policy from a women's human rights perspective and on the ongoing debate on their protection from severe exploitation regime also in relation to the discourse on trafficking. In Italy the debate is of particularly interest even if it remains largely under-researched.